2018
DOI: 10.1172/jci.insight.121326
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale plasma lipidomic profiling identifies lipids that predict cardiovascular events in secondary prevention

Abstract: Bristol-Myers Squibb, the National Health and Medical Research Council of Australia (grants 211086, 358395, and 1029754), and the Operational Infrastructure Support Program of the Victorian government of Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 37 publications
4
72
0
1
Order By: Relevance
“…The findings were first documented in the LURIC study [23] and replicated in the ATHEROREMO-IVUS study [28,29]. FINRISK 2002 study, Corogene study, PREDIMED trial, ADVANCE study, and LIPID study consistently confirmed the findings [24,26,[30][31][32].…”
Section: Yesmentioning
confidence: 68%
See 4 more Smart Citations
“…The findings were first documented in the LURIC study [23] and replicated in the ATHEROREMO-IVUS study [28,29]. FINRISK 2002 study, Corogene study, PREDIMED trial, ADVANCE study, and LIPID study consistently confirmed the findings [24,26,[30][31][32].…”
Section: Yesmentioning
confidence: 68%
“…The findings were observed in the LURIC study, WHI, PREDIMED trial, ADVANCE trial, and LIPID study [23,24,26,[32][33][34], and the associations persisted after adjusting for HDL-c and LDL-c.…”
Section: Yesmentioning
confidence: 74%
See 3 more Smart Citations